2020
DOI: 10.1016/j.bonr.2020.100733
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cortical bone thickness increases stress and strain in the female femoral diaphysis analyzed by a CT-based finite element method: Implications for the anatomical background of fatigue fracture of the femur

Abstract: The incidence of hip fractures is increasing in Japan and is high among women older than 70 years. While osteoporosis has been identified as one of the causative factors of fracture, atypical femoral fracture has emerged as a potential complication of bisphosphonate therapy. Atypical femoral fracture is prevalent among Asian women and has been attributed to morphological parameters. Age-related decreases in the morphological parameters of the femoral diaphysis, such as cortical bone thickness, cortical cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
2
12
1
Order By: Relevance
“…The results also indicate greater bone strain values on the buccal cortical plate as compared to the lingual cortical plate irrespective of the implant diameter and density of bone. This is may be due to the fact that buccal cortical plate is relatively thinner when compared to the lingual cortical plate [ 16 ]. The results also indicate greater bone strain values in the D2 type of bone as compared to the D3 type of bone.…”
Section: Discussionmentioning
confidence: 99%
“…The results also indicate greater bone strain values on the buccal cortical plate as compared to the lingual cortical plate irrespective of the implant diameter and density of bone. This is may be due to the fact that buccal cortical plate is relatively thinner when compared to the lingual cortical plate [ 16 ]. The results also indicate greater bone strain values in the D2 type of bone as compared to the D3 type of bone.…”
Section: Discussionmentioning
confidence: 99%
“…However, as our previous studies have shown, the trends of age-related changes were different for diaphyseal peripheral border length and thickness of cortical bone. On the other hand, the thickness of cortical bone not peripheral border length was strongly correlated with the stress and strain applied to the femur with one-legged standing configuration estimated with the finite element method [ 11 ], suggesting that external measurement of femoral morphology alone is insufficient to estimate its function and that it is essential to analyze its internal structure. For this reason, many analyses have been performed using CT [ 24 26 ], but measurement conditions must be uniform to compare results among different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Mean cortical bone thickness in each cross-section was also larger in Initial/Early and Late Jomon femurs than in modern femurs, both before and after standardization by diaphyseal length. A previous study reported that the mean thickness of the diaphysis in modern skeletal specimens correlated with the stresses and strains applied to the diaphysis during a one-legged stance [ 11 ]. Furthermore, mean thickness values were high in Jomon humans, indicating that their femurs were highly resistant to force, particularly that applied along the bone axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After FIF, it often causes hip pain, swelling, deformity, and limitation of movement [ 3 5 ]. If FIF is treated nonsurgically, it has many complications, and it is prone to complications such as pressure ulcers, lung infections, urinary tract infections, and deep vein thrombosis of the lower extremities, which can easily endanger the lives of patients [ 6 ]. Therefore, if the patient has no obvious surgical contraindications, for FIF, surgical treatment is recommended to stabilize the fracture end, shorten the patient's bedtime, and reduce the complications of the patient's bed [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%